Neprilysin: A Potential Therapeutic Target of Arterial Hypertension? (2020)
Arterial hypertension is the most prevalent chronic disease in the adult population of developed countries and it constitutes a significant risk factor in the development of cardiovascular disease, contributing to the emergence of many comorbidities, among which heart failure excels, a clinical syndrome that nowadays represents a major health problem with uncountable hospitalizations and the indolent course of which progressively worsens until quality of life decreases and lastly death occurs prematurely. In the light of this growing menace, each day more efforts are invested in the field of cardiovascular pharmacology, searching for new therapeutic options that allow us to modulate the physiological systems that appear among these pathologies. Therefore, in the later years, the study of natriuretic peptides has become so relevant, which mediate beneficial effects at the cardiovascular level such as diuresis, natriuresis, and decreasing cardiac remodeling; their metabolism is mediated by neprilysin, a metalloproteinase, widely expressed in the human and capable of catalyzing many substrates. The modulation of these functions has been studied by decades, giving room to Sacubitril, the first neprilysin inhibitor, which in conjunction with an angiotensin receptor blocker has provided a high efficacy and tolerability among patients with heart failure, for whom it has already been approved and recommended. Nonetheless, in the matter of arterial hypertension, significant findings have arisen that demonstrate the potential role that it will play among the pharmacological alternatives in the upcoming years.